Immunohistochemical peculiarities of cell adhesion molecules distribution in benign and malignant brain meningiomas - W. E. Voteva; S. I. Tertishniy (Zaporozhye State Medical University, 2014)
Aim. Meningiomas are widespread neoplasms of the brain, constituting 24-30% of all primary intracranial tumors. In order to determine the expression level of cell adhesion molecules β-catenin and E-cadherin in 20 specimens of brain with the help of immunohistochemical methods the expression of these molecules in benign and malignant meningiomas was investigated. Methods and results. The correlation relationship between the expression level of β-catenin and E-cadherin in malignant and benign meningiomas was determined. It is shown that the expression level of β-catenin in the different subtypes of benign meningiomas differs and, conversely, they have a similar expression level of E-cadherin. Conclusion. Most of benign meningiomas are characterized by significantly higher expression levels of cell adhesion molecules than anaplastic ones.